Initial Stress Differences Between Sliding and Sectional Mechanics with an Endosseous Implant as Anchorage: A 3-Dimensional Finite Element Analysis (2001)
ABSTRACT: Endosseous implants have been used as orthodontic anchorage in recent years. A 3-dimensional mathematical model was constructed that uses the finite element method, which simulated an endosseous implant and an upper canine with its periodontal ligament and cortical and cancellous bone. Levels of initial stress were measured during 2 types of canine retraction mechanics (friction and frictionless). The lower magnitude and more uniform stresses in the implant and its cortical bone were found to have a moment-force ratio (M/F) of 6.1:1, whereas the canine and its supporting structures exerted a M/F ratio of 10.3:1. On the basis of these results, when the anchor unit is an endosseous implant, it seems better to use a precalibrated retraction system without friction (T-loop) where a low load-deflection curve would be generated. (Angle Orthod 2001;71:247–256.)